myc protooncogene linked to retroviral promoter, but not to enhancer, transforms embryo cells. - Zhou, R P (1988)
To define conditions under which the chicken protooncogene p-myc is converted to a viral and possibly to a cellular transforming gene, we assayed transforming function of hybrid genes put together from cloned retroviral and p-myc elements and of p-myc genes isolated from spontaneous viral lymphomas. Transforming function was measured in quail embryo cells transfected with cloned myc genes. We found that only myc genes with a promoter of a retroviral long terminal repeat (LTR) located between the native p-myc promoter and the second p-myc exon have transforming function. Transforming efficiencies decreased with increasing lengths of unspliced sequences between the LTR and p-myc exon 2. p-myc DNAs with LTRs downstream of the coding region or upstream but in the opposite transcriptional orientation failed to transform embryo cells. Likewise, only those retroviral-p-myc combinations from chicken B-cell lymphomas with a LTR positioned as promoter upstream of p-myc exon 2 had transforming function. We conclude that substitution of a retroviral LTR for the promoter and for as yet poorly defined, untranscribed regulatory elements of p-myc is sufficient to convert chicken p-myc to a transforming gene. However, retroviral LTRs can only convert p-myc genes to embryo-cell-transforming genes from a limited number of positions, and not as position-independent enhancers. Further, we deduce that there are two classes of viral chicken B-cell lymphomas, those with and those without embryo-cell-transforming p-myc genes.